Design and simulation of a solar-hydrogen system for different situations - Ural, Zehra; Gencoglu, Muhsin Tunay (Pergamon-Elsevier Science Ltd, 2014)
In recent years, hybrid photovoltaic fuel cell energy systems have been popular as energy production systems for different applications. A typical solar-hydrogen system can be modeled the electricity supplied by PV panels is used to meet the demand directly to the maximum extent possible. If there is any surplus PV power over demand, and capacity left in the tank for accommodating additional hydrogen, this surplus power is supplied to the electrolyser to produce hydrogen for storage. When the output of the PV array is not sufficient to supply the demand, the fuel cell draws on hydrogen from storage and produces electricity to meet the supply deficit. In this study, solar-hydrogen systems and their application areas have been examined with emphasizing importance of renewable energy sources for electrical energy production. A hybrid system consists of solar cell and fuel cell have been designed and simulated in Matlab-Simulink. Firstly, the models of fuel cell, solar cell, electrolyser, DC DC converter and inverter have been constituted separately in Matlab-Simulink. Then, system model have been obtained with combining of these models. Characteristics of output voltage and current have been investigated with using the acquired model for different loads. Copyright (C) 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: PEM fuel cell; PV model; Solar hydrogen system; Electrolyser